Refugees in our Own Land - Ariege Muallem (International Institute of Islamic Thought, 2003)
Refugees in our Own Land narrates the author’s life between October and December 2000, when she was married and living in the West Bank’s Dheisheh refugee camp. The book creates a new respect for the refugees among whom she lived and gives the reader a glimpse of the incredible difficulties of their everyday lives. The book is divided into two parts. The first part chronicles Hamzeh’s life during October 4-December 4, 2000: her personal life and that of her friends in Dheisheh, as well as current political events and how they affect the life of the refugees in the camp. These almost daily entries were actually e-mailed to a large number of people while she was still living in Dheisheh. The second half of the book is a series of short unrelated stories and articles, written between 1988 and March 2000, that highlight events that brought her to Dheisheh and explain other events and people in her life. Their order is a bit odd. After the reader gets used to Hamzeh’s life in the camp, she abruptly ends her entries by describing how she left the camp and then, just when the reader wants to know what happened next, she starts relating the events that transpired 2 years ago prior to her journey to the West Bank. There is no mention of a husband there, and then all of a sudden she goes from living in the United States to ending up in Dheisheh. How she got there, unfortunately, is never explained. The lack of details concerning such important transitions is quite frustrating. Although she may have considered them “too personal” to include, it resulted in frustration on the reader’s part. One success, however, is her exposure of the humanity of people who so often are dismissed by the world as “refugees.” She mentions their names and describes their faces and personalities, thereby giving the reader an ...